PELAKSANAAN BIMBINGAN KELOMPOK OLEH GURU BK BAGI SISWA BERPRESTASI BELAJAR RENDAH KELAS VIII SMPN 1 SOMPAK - Marlinda, Peni; Asrori, Muhammad; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to obtain an overview to analyze how the implementation of group guidance by counseling and counseling teachers for low-achieving learners, and how the stage of formation, transition, activity, and termination of group guidance for low-achieving learners, and how students respond after getting service group guidance on low learning achievement. The method used in this research is descriptive method in the form of survey study that is the procedure with the problems investigated by describing or describing the implementation of group guidance by teacher guidance and counseling for low-achieving learners in class VIII SMP Negeri 1 Sompak, and explained descriptively. Data collection in this study using questionnaire. Based on the results of data analysis of group guidance by guidance and counseling for low achieving students in grade VIII SMP Negeri 1 Sompak achieve actual score 518 and ideal score 1175 with 44% percentage of category "good enough". Which means showing the implementation of group guidance by teachers guidance and counseling for low-achieving learners in grade VIII students SMP Negeri 1 Sompak is good enough.Keywords: Group Guidance, Low Learning Achievement